1996
DOI: 10.1007/bf00165484
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of metastatic brain tumors

Abstract: The most common structural neurologic complication of systemic cancer is brain metastasis. For the most part, treatment is palliative because the majority of patients (> or = 50%) have uncontrollable systemic cancer. However, for patients in whom the only metastasis is to the brain, death is more likely to result from the metastasis than from the systemic disease; hence, treatment of the metastasis is vitally important. Although radiotherapy is generally considered the preferred treatment, surgical removal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1
11

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 40 publications
0
34
1
11
Order By: Relevance
“…Melanoma and small cell lung cancer are two of the most common tumors metastasizing to the brain. Twenty-five percent of cerebral metastases are superficial, occurring at the cortical-white junction interface, 25 to 40% percent of patients demonstrate solitary lesions, and the remainder have widely disseminated disease [4,34,35]. Up to half of metastatic brain lesions due to melanoma will bleed in either a subarachnoid or an intracerebral location.…”
Section: Brain and Spinal Cord Metastasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanoma and small cell lung cancer are two of the most common tumors metastasizing to the brain. Twenty-five percent of cerebral metastases are superficial, occurring at the cortical-white junction interface, 25 to 40% percent of patients demonstrate solitary lesions, and the remainder have widely disseminated disease [4,34,35]. Up to half of metastatic brain lesions due to melanoma will bleed in either a subarachnoid or an intracerebral location.…”
Section: Brain and Spinal Cord Metastasesmentioning
confidence: 99%
“…Initial emergent treatment involves a short-term corticosteroid course to reduce edema surrounding the tumor while further workup is performed. Neurosurgery is a well-established treatment as the only possible chance for cure or long-term survival [34]-it can be offered to 5 to 10% of patients with brain metastases. Factors affecting long-term survival include isolated brain metastases treated with surgery or combined with radiotherapy, long-term diseasefree survival, absence of extracranial disease, and only mild symptoms at craniotomy [9,34,36].…”
Section: Brain and Spinal Cord Metastasesmentioning
confidence: 99%
“…Standard treatment modalities for metastases are surgery, radiotherapy, and/or stereotactic radiosurgery [76,77,78,79,80]. A summary of the various studies reporting the use of LITT for brain metastases and radiation necrosis is given in table 2.…”
Section: Clinical Application Of Litt In Brain Lesionsmentioning
confidence: 99%
“…These data were confirmed by Arbit et al [66] when evaluating 109 patients with recurrent brain metastases of NSCLC. Sawaya et al [37] stated that whenever possible surgery should remain the treatment of choice, even in recurrent brain metastases. Wong et al [67] reported on 86 patients who were reirradiated for progressive brain metastases.…”
Section: Treatment Of Recurrent Brain Metastasesmentioning
confidence: 99%
“…Radiotherapy can be preserved for recurrent tumor growth. Several investigators evaluated the efficacy of WBRT in addition to surgery versus WBRT alone [5,[14][15][16][36][37][38][39]. To date, the overall results of surgical treatment strategies plus adjuvant WBRT indicate that WBRT alone as treatment is inferior to the combined treatment [5,14].…”
Section: Radiotherapymentioning
confidence: 99%